Skin lesion, which are not always remember - Cywińska-Bernas, Agnieszka; Zeman, Krzysztof (Przewodnik Lekarza/Guide for GPs, 2011)
Skin which is a specialized organ in the human body beyond the protective function also fulfills an important role in immunological processes. It is a location of changes and symptoms in diseases of different etiologies, including systemic. A detailed examination of the skin of the whole body is an important component of patient examination. It is worth remembering not only the most common skin diseases but also for dermatological symptoms that occur less frequently. The paper presents a specific skin lesions which could be observed in children with selected infectious diseases (scabies, hand, foot and mouth disease, fungal infection), autoimmunity (vasculitis) and after drug reactions.